Contest Corner: The 2016 State Tournament of Mathematics Results - Flick, Michael; Kuchey, Debora (Ohio Journal of School Mathematics, 2017)
In this article, the authors summarize results from the 2016 Ohio Mathematics Tournament. Included in the summary are sample tasks from the contest.